Islamic Viewpoint on The Vulnerability of Women with Double Burdens in Families during the Covid-19 Pandemic in Depok City - Nadya Kharima; Radhina Fasya; Yulianti (Islamic Studies Journal for Social Transformation, 2021)
Based on existing data and analysis, many have suggested that women bear more burdens than men in theirdomestic lives when the covid-19 pandemic occurs. Because of this, there is a discourse of gender injustice due to theexcessive double burden of women compared to men in the household in this pandemic period. Then how Islamactually views the vulnerability of women in bearing the double burden. Therefore, the author wants to raise thetheme of how the Islamic point of view of the vulnerability of women with double burdens in the family during thecovid-19 pandemic in Depok City. Where the author also tries to study in research that uses qualitative research.This qualitative research aims to explain existing phenomena by collecting data using interview methods withwomen in Depok City and literature studies that aim to study various literature related to how Islamic viewpointson the vulnerability of women with double burdens in the family. The result of this study is the vulnerability ofwomen with a double burden in the family is already starting awareness to share roles, but due to pandemicsactually cause limited roles that must be borne by men and women are difficult to equalize. While in Islam viewmen and women have the same or equal position in the affairs of household, where there is expected to be anagreement between the two parties. So it is important to build knowledge from the point of view of Islam inproviding a fair division for men and women to have a role in the family.